ZNACZENIE KOORDYNACJI I WSPÓŁPRACY W ZAKRESIE ZWALCZANIA KARTELI ANTYKONKURENCYJNYCH W PERSPEKTYWIE MIĘDZYNARODOWEJ - Swora, Mariusz; Sachajko, Marek (Wydział Prawa i Administracji UAM, 2006)
The paper deals with international implications of anti-competitive cartel law enforcement. The main issue discussed in the paper is the effectiveness of international legal tools regulating anti-cartel laws enforcement, including, in particular, the leniency programmes. The authors examine the activities of international organisations (especially OECD and ICN) concerning fighting cartels, the US and EU approach to international cooperation within the World Trade Organization, extraterritorial enforcement of the US and EU laws against cartels and the effectiveness of leniency programmes. The authors are skeptical about the possibility of adopting a multilateral antitrust agreement at the WTO, considering particularly US approach. On the other hand, there are legal tools (mainly bilateral agreements) that enable fighting international cartels within a decentralized antitrust law enforcement system. Apart from bilateral agreements, actions against cartels are also taken by certain states through extraterritorial enforcement o f anti - cartel laws. The authors claim that within the system of domestic anti-cartel laws it is necessary to take measures to ensure that anti-cartel sanctions, including those available in criminal law, are effective.
THE ROLE OF CO-ORDINATION AND CO-OPERATION IN ANTICOMPETITIVE CARTEL LAWS ENFORCEMENT - AN INTERNATIONAL PERSPECTIVE